OPTIMALISASI PENGELOLAAN ASET WAKAF DI KECAMATAN PONOROGO - Muh. Shulthon Rachmandhani (IAIN Ponorogo, 2022)
AbstractNadzir is an important element in the wakalah waqf process. Waqfs wishing to donate their assets as waqf must choose a nadzir as the recipient of the assets as well as a trusted party to manage it. Nadzir is divided into three types, namely: foundations, legal entities, and individuals. Given the importance of the existence of the nadzir in the waqf procession, an appropriate strategy is needed to maintain the existence of waqf assets so that they are always beneficial to the waqif, as well as to the people. Therefore, this article aims to reveal the implementation of the nadzir strategy in optimizing waqf assets in the Ponorogo District area. The research method used in writing this research article is a multi-site qualitative research method, which was conducted in three different mosques, namely: 1. As-Salam Sunan Muria Bangunsari Ponorogo Mosque which is a representation of waqf assets managed by individuals. 2. K.H. Mosque Ahmad Dahlan Nologaten Ponorogo which is a representation of waqf assets managed by the Muhammadiyah organization. 3. Nadhlatul Ulama Sultan Agung Bangunsari Ponorogo Mosque which represents waqf assets managed by the Nadhlatul Ulama organization. Data collection techniques were carried out through interviews, participant observation, and documentation. The results of the study show that efforts to optimize the management of waqf assets are carried out by each nadzir by applying the blue ocean strategy management model based on the environmental characteristics of the organizational culture. ABSTRAKNadzir merupakan elemen yang penting dalam proses wakalah wakaf. Wakif yang hendak mewakafkan harta kekayaannya diharuskan untuk memilih nadzir sebagai penerima harta tersebut sekaligus sebagai pihak yang diamanati untuk mengelolanya . Nadzir dibedakan ke dalam tiga jenis yaitu: yayasan, badan hukum, dan perorangan. Mengingat pentingnya eksistensi nadzir dalam prosesi wakaf maka dibutuhkan strategi yang tepat untuk menjaga eksistensi harta wakaf tersebut agar selalu bermanfaat bagi wakif, serta bagi umat. Oleh karena itu, artikel ini bertujuan untuk mengungkap implementasi strategi nadzir dalam mengoptimalkan aset wakaf di kecamatan Ponorogo. Metode penelitian yang digunakan dalam menulis artikel penelitian ini adalah metode penelitian kualitatif berjenis multisitus, yang dilakukan di tiga masjid yang berbeda yaitu: 1. Masjid As-Salam Sunan Muria Bangunsari Ponorogo yang merupakan representasi dari aset wakaf yang dikelola oleh perorangan. 2. Masjid K. H. Ahmad Dahlan Nologaten Ponorogo yang merupakan repesentasi dari aset wakaf yang dikelola oleh organisasi Muhammadiyah. 3. Masjid Nadhlatul Ulama Sultan Agung Bangunsari Ponorogo yang merupakan representasi dari aset wakaf yang dikelola oleh organisasi Nadhlatul Ulama . Teknik pengumpulan data dilakukan melalui teknik wawancara, observasi patisipan, dan dokumentasi. Hasil penelitian menunjukkan bahwa upaya optimalisasi pengelolaan harta wakaf yang dilakukan oleh masing-masing nadzir dengan cara menerapkan model manajemen strategi blue ocean strategy berbasis karakteristik lingkungan budaya organisasi.